LAUTENBERG TO PUSH FOR 3-YEAR SMOKING BAN ON DOMESTIC FLIGHTS OF 2 HOURS OR LESS - LAUTENBERG, FRANK (Tufts Archival Research Center, 2007)
Press release announcing the plan of Senator Frank Lautenberg to try and implement a three year smoking ban on domestic flights that are two hours or less.